ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGUSAHA SENTRA INDUSTRI KECIL DI KABUPATEN KERINCI - Chatra, Afdhal (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study discusses the determinants that affect the income of small industrial center entrepreneurs in Kerinci Regency in 2020. The data used are secondary data, derived from data obtained from the Central Statistics Agency, the Ministry of Trade and Industry and 50 small industrial center entrepreneurs in Kerinci Regency. The analytical method used is qualitative and quantitative methods, because the analysis is in accordance with the desired results, namely how much the independent variable affects the dependent variable. Based on the results of research on the factors that affect the income of small industrial center entrepreneurs in Kerinci Regency whose parameters using the OLS (Ordinary least squares) method have revealed the influence of business capital, number of hours worked, work experience and education as a whole affect the income of small industrial center entrepreneurs in Kerinci Regency. This can be seen from the simultaneous testing that has been carried out, namely the value of f statistic > f table. Thus, an increase in one's work productivity will further increase the increase in yield and ultimately increase the income of small industrial center entrepreneurs in Kerinci Regency